The microplastics in the marine environment: origin, hazardous effects and possible biological solutions: a review - Yap, How Swen; Yasid, Nur Adeela (Hibiscus Publisher, 2024)
This review explores the escalating issue of marine microplastic pollution, a consequence of the extensive use of high molecular weight polymers in various industries. It delves into the origins, types, and environmental impacts of microplastics, particularly focusing on primary and secondary forms found in marine ecosystems. The study highlights the significant role of microplastics in global plastic production and their contribution to marine pollution, exacerbated by poor waste management and environmental factors. The review also examines the ecotoxicological effects of microplastics on marine life, noting species-specific responses ranging from physical blockages to chemical toxicity, often worsened by the interaction with other pollutants. Furthermore, it discusses innovative biological approaches for microplastic remediation, including the potential roles of microorganisms and certain marine and land animals in degrading or accumulating microplastics. This comprehensive analysis emphasizes the urgent need for effective waste management strategies, recycling efforts, and sustainable alternatives to conventional plastics, aiming to balance industrial and consumer demands with environmental conservation and address the critical issue of marine microplastic pollution.